Public Event: Commons Governance Workshop: Michel Bauwens of the P2P Foundation - Ackerley, Christine Rose (Stream: Interdisciplinary Journal of Communication, 2016)
The Global Communication M.A. Double Degree Program is holding Program's Colloquium Presentation - Part III: Commons Governance Workshop with Michel Bauwens of the P2P Foundation on Thursday, March 17, from 10:00am to noon at Vancouver Harbour Center Campus Room 2250. For details, please see the attached PDF.